A new subspecies of Calisto disjunctus Núñez & Barro (Lepidoptera: Nymphalidae: Satyrinae) from Western Cuba, with a key to the Cuban members of the genus - Álvarez, Yosiel; Núñez, Rayner (Zootaxa, 2021)
Calisto disjunctus hersheyi ssp. n. is described from western Cuba. Additionally, a dichotomous key including all described Cuban taxa of the herophile species group of Calisto is given together with illustrations of live specimens of most taxa.